Introduction to sectional anatomy - Madden, Michael E. (Wolters Kluwer Health : Lippincott Williams & Wilkins, 2013)
"By using Introduction to Sectional Anatomy, the reader will be able to view images from several patients in each region of the body, thereby allowing them to compare the anatomical appearance. Similarly, the patient images will be shown using a variety of current imaging modalities such as CT, MR, PET/CT, and ultrasound, including three-dimensional (3D) imaging of vascular and bony anatomy"--Provided by publisher